Individual Technical Academic Supervision Using Digital Technology - Rusmaniar, Rusmaniar; Widiyatsih, Tri; Setiyo, Herry (PPSDP International Journal of Education, 2023)
The education sector is currently undergoing changes toward digitization, because of technological developments and the impact of the pandemic. In the supervision sector, learning quality is inextricably linked to these demands. As a result, school principals’ primary option for facilitating academic supervision implementation is digitization. The purpose of this research is to examine the implementation of individual technical academic supervision based on digitalization in junior high schools. The qualitative method was used in this study. Data collection methods include observation, interviews, and a review of the literature. The descriptive qualitative analysis was used to analyze the data. The principal used digital-based instruments to carry out several individual supervision activities such as class visits, class observations, individual meetings, inter-class visits, and self-assessment. Digital-based academic supervision activities are more focused on a comprehensive assessment of the quality of teacher assignment implementation rather than just administrative completeness. The use of digital instruments in the delivery of individual technical academic supervision has a positive impact on learning quality.